Reduced graphene oxide/TEMPO-nanocellulose nanohybrid based electrochemical biosensor for the determination of Mycobacterium tuberculosis - Mat Zaid, Mohd Hazani; Abdullah, Jaafar; Yusof, Nor Azah; Wasoh, Helmi; Sulaiman, Yusran; Md Noh, Mohd Fairulnizal; Issa, Rahizan (Wiley, 2020)
A novel peptide nuclide acid (PNA) electrochemical biosensor based on reduced graphene oxide (NH2-rGO)/2,2,6,6-tetramethylpiperidin-1-yl)oxyl nanocrystalline cellulose (TEMPO-NCC) for the detection of Mycobacterium tuberculosis (M. Tuberculosis) is described. In this study, the nanohybrid films NH2-rGO/TEMPO-NCC were immobilized onto screen-printed carbon electrode (SPE) via a simple drop-coating method. The electrochemical characterization of the designed electrode was investigated using cyclic voltammetry (CV) and impedance spectroscopy (EIS). Meanwhile, the sensitivity and selectivity of the designed biosensor against M. tuberculosis were measured by the differential pulse voltammetry (DPV). The response of the PNA probe-modified (NH2-rGO)/TEMPO-NCC demonstrated that the fabricated biosensor was able to distinguish between complementary, noncomplementary, and one-base mismatch DNA sequences using methylene blue (MB) as the electrochemical indicator. The developed electrochemical biosensor exhibited a linear calibration curve in the concentration range of 1 × 10−8 M to 1 × 10−13 M with the limit of detection of 3.14 × 10−14 M. The developed electrochemical biosensor has also been tested with a polymerase chain reaction (PCR) product of M. tuberculosis DNA which has shown successful results in distinguishing between negative and positive samples of M. tuberculosis.